What Visitors Want From Urban Parks: Diversity, Utility, Serendipity - Taylor, Lucy; Leckey, Erin H.; Lead, Peter J.; Hochuli, Dieter F. (Frontiers in Environmental Science, 2020)
Urban parks may provide a range of ecosystem services, but community perspectives can influence the conservation of parks and their biodiversity. Cultural ecosystem services, or the non-material benefits that people receive from nature, can prompt a park’s use and motivate a management response from local government. Our study aimed to explore the tacit biodiversity of a park, or the nature observed during a park visit, and understand why people visit urban parks, what they notice there, and how being there makes them feel. Combining both human and more-than-human aspects, we carried out park surveys that comprised an ecological survey and short, 3-question interview with park visitors. The park surveys were carried out in six parks in Melbourne and Sydney, Australia, and Auckland and Wellington, New Zealand. While the biodiversity of species in parks differed significantly within and between cities, we found no consistent relationships between park biodiversity and the numbers of people in parks nor how being in the parks made participants feel. Some park visitors did say that their reason for being in the park was to engage with nature, but other reasons were also listed, such as to meet friends or use specific park facilities, such as gym equipment or playgrounds. Park visitors valued a diverse range of services and natural utilities, such as shade, from their visit. Many interactions were also serendipitous for visitors due to the proximity of urban parks near residential areas, businesses and transport hubs. We conclude that although the use of parks was not directly tied to biodiversity per se, visitors considered them to be places where they can interact with nature in a range of ways.